Can Continuous Positive Airway Pressure Reduce the Risk of Stroke in Obstructive Sleep Apnea Patients? A Systematic Review and Meta-Analysis. - Yeshin Kim; Yong Seo Koo; Hee Young Lee; Seo-Young Lee (PLoS ONE)
Background and purpose Obstructive sleep apnea (OSA) has been shown to increase the risk of stroke. Although continuous positive airway pressure (CPAP) is considered the treatment of choice for OSA, whether treating OSA with CPAP reduces the risk of stroke remains unclear. We aimed to evaluate the effects of CPAP on incidence of stroke in patients with OSA. Materials and methods We conducted a systematic review and meta-analysis of all published studies that provided the number of incident strokes in OSA patients in light of their treatment status with CPAP. Results We identified 8 relevant studies: one randomized controlled study (RCT), 5 cohort studies, and 2 studies using administrative health data. The two overlapping cohort studies in women and the elderly and the 2 studies using administrative health data had analyzed the impact of CPAP on stroke apart from cardiac events, whereas the others had focused on the overall cardiovascular events. Based on a meta-analysis of the cohort studies, treatment with CPAP was associated with a lower incidence of stroke and cardiac events with relative risks of 0.27 [0.14-0.53], and 0.54 [0.38-0.75], respectively, although this could not be reproduced in the RCT and the studies using administrative data. Conclusions Treating with CPAP in patients with OSA might decrease the risk of stroke, although there is some conflicting evidence. Such effect was more pronounced in stroke than in cardiac events. Future studies analyzing stroke apart from cardiac disease would be of interest.